Outcomes of beta-blocker pharmacotherapy in patients with heart failure - Maletin Sanja D.; Maletin Srđan M.; Baltić Milan V.; Krtinić Dane A.; Mićanović Branimir B.; Todorović Nemanja B.; Milijašević Boris Ž. (Srpsko lekarsko drustvo, 2024)
Introduction: Heart failure is characterized by a high prevalence both in our country and in the world. Patients with heart failure have an impaired quality of life, are prone to rehospitalization and have a higher mortality rate. Adequate pharmacotherapy should be set in a proper manner and in accordance with the latest knowledge. Aim: The aim of the research was to examine the role of beta blockers in patients with HF (ischemic and non-ischemic etiology) as one of the key drugs in their treatment. Material and Methods: The criteria for the inclusion of patients in the study was an established ejection fraction lower than 30%, they were divided depending into two equal groups, one with ischemic and other with non-ischemic heart failure. Thirty patients participated in the study. Data on beta blocker therapy and treatment outcomes were observed and compared with the recommendations given by the guidelines of the European Society of Cardiology. Results: The study included more men than women. The largest number of patients were treated with bisoprolol, followed by metoprolol and carvedilol. Regardless of the etiology of heart failure the majority of the patients were treated with a dose of 2.5 miligrams of bisoprolol. Atrial fibrillation was present in slightly less than a third of patients, disregarding the etiology of HF. In the three-year follow-up of our patients, 46.4% died from nonischemic cardiomyopathy, or 13.2% from ischemic cardiomyopathy. Conclusion: Most patients were on appropriate beta-blocker therapy according to guidelines. Atrial fibrillation has been confirmed as a poor prognostic parameter. A three-year follow-up of our patients showed a high percentage of deaths, but no association of betablocker dose with poor outcomes.